About heat treatment - Santos De la Cruz, Eulogio (2000)
The treatment of metals and alloys is a complex technological process comprising the steps of heating, holding and cooling in the process the complete transformation of structural phases, followed by a velicidad adequate cooling is achieved, which are modified sis properties which depend on the nature, size and distribution of the structural constituents that are related to the yield strength, breaking strength, elongation and energy absorption.